Job Satisfaction and Intention to Leave among Middle-Level Managers of SMEs in Dubai, UAE - Basma Waleed Kashmoola; Amiruddin Ahamat (Indonesian Management and Accounting Research, 2020)
In Dubai, United Arab Emirate (UAE), the Small and Medium Enterprises (SMEs) in the construction sector have a shortfall of 500,000 skilled employees because of the lack of job satisfaction and top management support, which prompt workers to leave their places of employment. Thus, this study investigated the effect of top management support (TMS) as an organizational factor on the relationship between job satisfaction and the intention to leave among the middle level managers in the construction sector of Dubai, UAE. To test the relationship among the variables, this study adopted a quantitative design and data was collected from 120 middle level managers of SMEs. The Partial Least Squares – Structural Equation Modelling (PLS-SEM) technique was adopted in the data analysis. According to the outcome, the relationship between 4 facets of job satisfaction and the intention to leave among the middle level managers of SMEs was established. The study also found statistical support for the moderating effect of TMS on the relationship between 2 facets of job satisfaction and the intention to leave among the middle level managers of SMEs.